UNSCARRED UTERINE COMPLETE RUPTURE IN A CASE OF FULL-TERM PRIMIPAROUS PREGNANCY (Journal of Forensic Medicine & Toxicology, 2024)
Rupture of gravid uterus is mainly associated with previous uterine surgeries with presence of scars. Intact unscarred uterus rupture is rare entity during pregnancy. Only few cases have documented correlation with some other risk factors than surgery. History of trauma is important risk factor. Most of these cases are not diagnosed in proper time due to non-specific clinical presentation, leading to high mortality of mother and baby. Abdominal pain due to impending uterine rupture especially in third trimester can be confused with the labor pain and furthers delays the diagnosis. We encountered a rare case of Maternal death with 38 weeks gestation brought dead in the trauma and emergency department of tertiary care center of Dibrugarh, Assam. She had history of accidental fall on the road. We found complete full thickness rupture of anterior wall of uterus with hemoperitoneum and fetal demise. Hence, autopsy findings of the case have been presented here with relevant literature review.
Keywords: Gravid uterus; Unscarred; Rupture; Labor pain; Trauma; Hemoperitoneum